Ways to Create a Mock-Up Project and Prepare for Mock-Up Making Classes (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
With the growth of the quality of life there is a need to build modern, quality housing, using modern building materials, the labour of qualified builders becomes in demand and highly paid. This situation forces us to approach the process of building design with special care, to strive for a longer life of both architectural objects and complexes, as well as residential, public interiors and landscaping. The main task becomes the guarantee of quality and safe construction, i.e. risk reduction. The only way to evaluate the idea at the project stage is to create its computer model or traditional layout. Mastering the basics of modelling in the training and education of specialists: architects, designers, restorers is one of the most important factors in the modern education of higher school students.